2006
DOI: 10.2136/sssaj2005.0058
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilization and Cropping System Impacts on Soil Quality in Midwestern Mollisols

Abstract: High grain production of corn (Zea mays L.) can be maintained by adding inorganic N fertilizer, and also by using crop rotations that include alfalfa (Medicago sativa L.), but the relative impact of these management practices on soil quality is uncertain. We examined the effects on soil of N fertilization rate (0, 90, 180, 270 kg ha −1 , corn phase only) in four cropping systems: CC, continuous corn; CS, corn-soybean [Glycine max (L.) Merr.]; CCOA, corn-corn-oat (Avena sativa L.)-alfalfa; and corn-oat-alfalfa-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 30 publications
3
65
0
4
Order By: Relevance
“…On the contrary, the effect of nitrogen fertilization is significant, although the differences are too small (1 cmol + kg -1 for the upper 5 cm layer and 0.6 for the 20 cm layer) to assume agronomic importance. No-till generally determines an increase in CEC parallel to the organic matter, whereas large amounts of nitrogen fertilizer have a tendency to reduce it (Russell et al, 2006). In this trial, the small CEC increases in the N 2 subplots could be attributed to the organic matter increases in the upper 10 cm of the soil profile.…”
Section: Resultsmentioning
confidence: 56%
“…On the contrary, the effect of nitrogen fertilization is significant, although the differences are too small (1 cmol + kg -1 for the upper 5 cm layer and 0.6 for the 20 cm layer) to assume agronomic importance. No-till generally determines an increase in CEC parallel to the organic matter, whereas large amounts of nitrogen fertilizer have a tendency to reduce it (Russell et al, 2006). In this trial, the small CEC increases in the N 2 subplots could be attributed to the organic matter increases in the upper 10 cm of the soil profile.…”
Section: Resultsmentioning
confidence: 56%
“…Russell [34] studied the fertilization addition under different N fertilization rates (0, 90, 180 and 270 kg/ha), and found that for continuous corn cropping systems, N fertilizer additions resulted in remarkably lower soil pH (0 to 15 cm depth), lower exchangeable Ca, Mg and K, and CEC [34]. In our study, the result of the ANOVA showed that the difference between the two groups was insignificant.…”
Section: Association With Environmental Factors and Agricultural Manamentioning
confidence: 46%
“…Different fertilization treatments have different effects on soil properties in different crop systems, increasing or decreasing the contents of some soil nutrients [34]. Russell [34] studied the fertilization addition under different N fertilization rates (0, 90, 180 and 270 kg/ha), and found that for continuous corn cropping systems, N fertilizer additions resulted in remarkably lower soil pH (0 to 15 cm depth), lower exchangeable Ca, Mg and K, and CEC [34].…”
Section: Association With Environmental Factors and Agricultural Manamentioning
confidence: 99%
“…It is also a high-water use plant, and with its deep roots, serves to draw down the water table to a much greater depth than annual crops, reducing the risk of secondary salinity associated with a shallow water table (Ridley et al 2001). As a nitrogen-fixing plant, it may also provide a fertility benefit to subsequent annual crops (Russell et al 2006). Alfalfa is the most widely researched forage crop for both water and salinity management, but other crops may be more appropriate under excess water conditions.…”
Section: Crop Selection and Rotationsmentioning
confidence: 99%